AKUNTABILITAS TERHADAP PEMBAYARAN PAJAK BUMI DAN BANGUNAN DI DESA DAMAI KECAMATAN WATANG SIDENRENG KABUPATEN SIDENRENG RAPPANG - Rina Rukmanti; Adam Latif; Akhyaruddin Hakim (FISIP Universitas Muhammadiyah Sidenreng Rappang, 2020)
The level of accountability forand building tax payments in Damai Village, Watang Sidenreng District, Sidenreng Rappang District, and to find out the factors that influence the level of community awareness in paying land taxes and Buildings in Damai Village, Watang Sidenreng District, Sidenreng Rappang Regency. The population in this study was 1,486 where the sampling used was Probability Sampling with a random sampling technique using aformula of Yount 5% with a total sample of 74. This study used a Quantitative Descriptive Method. Data collection techniques used through observation, questionnaires (questionnaire), documentation and interviews. The data analysis technique used is Descriptive Statistics, data quality test, classic assumption test using SPSS 21 and Likert Scale. The results showed that accountability for land and building tax payments in the peaceful village of Watang Sidenreng sub-district was categorized as